2020
DOI: 10.1016/j.janxdis.2020.102268
|View full text |Cite
|
Sign up to set email alerts
|

Incremental validity of coronaphobia: Coronavirus anxiety explains depression, generalized anxiety, and death anxiety

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
263
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(328 citation statements)
references
References 16 publications
20
263
1
16
Order By: Relevance
“…Nurses participating in the study indicated the frequency of symptoms experienced in a 5-point Likert-type scale (0 [not at all] to 4 [nearly every day]). The scale had an outstanding predictive validity, as evidenced by a positive association with disability and psychological distress (Lee et al, 2020), and excellent reliability, with an internal consistency of 0.93 in a previous study (Lee et al, 2020) and a Cronbach's alpha of 0.87 in the present study.…”
Section: Instrumentationsupporting
confidence: 70%
See 1 more Smart Citation
“…Nurses participating in the study indicated the frequency of symptoms experienced in a 5-point Likert-type scale (0 [not at all] to 4 [nearly every day]). The scale had an outstanding predictive validity, as evidenced by a positive association with disability and psychological distress (Lee et al, 2020), and excellent reliability, with an internal consistency of 0.93 in a previous study (Lee et al, 2020) and a Cronbach's alpha of 0.87 in the present study.…”
Section: Instrumentationsupporting
confidence: 70%
“…Possible scores for this scale ranged from 5 to 25. The scale discriminates between those with dysfunctional anxiety andnon-anxiety using an optimized cut-off score of 9(Lee et al, 2020).…”
mentioning
confidence: 99%
“… Noyes and colleagues (2005) also reported a strong correlation between health anxiety and negative temperament (which is similar to the Big Five's personality trait of neuroticism). In the afore mentioned study by Lee and colleagues (2020a) , undertaken in the early phases of the pandemic, neuroticism was also found to be correlated with health anxiety. This study also indicated a positive correlation between neuroticism and COVID-19 anxiety.…”
Section: The Big Five Personality Traits As Predictors Of Negative Afmentioning
confidence: 89%
“…In a very recent study undertaken at the height of the pandemic (April 2020) Lee and colleagues (2020a) showed that neuroticism predicted both generalised anxiety and depressive symptoms controlling for a wide array of sociodemographic variables (e.g. age, gender, etc.…”
Section: The Big Five Personality Traits As Predictors Of Negative Afmentioning
confidence: 99%
“…Previous studies have highlighted health anxiety as a potential risk factor for heightened virus anxiety [ 13 , 15 , 16 , 17 , 18 , 19 , 20 ], but partly lacked a differentiation between health anxiety pre and during COVID-19. In the present study, we confirmed the role of health anxiety in SARS-CoV-2 related anxiety and additionally showed that both pre-existing (pre) (retrospectively assessed) and emerging (during) health anxiety intensified the linear increase of SARS-CoV-2 related anxiety during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%